METHODOLOGY FOR STUDYING NATIONAL COLORISTICS IN MODERN POETRY: A CASE STUDY OF CONTEMPORARY LITERATURE IN KAZAKHSTAN - Dina, Sabirova; Saule, Abisheva; Madina, Moldagali; Mekhirnissa, Khavaidarova; Dina, Polyak (Journal of Posthumanism, 2025)
The study of national coloristics in modern poetry involves the examination of how language reflects cultural identity, national consciousness, and the socio- political landscape. This research paper presents a methodological framework for studying national coloristics in the poetry of Kazakhstan, focusing on contemporary poets and their engagement with national heritage, historical memory, and cultural symbols. The research explores how language, symbolism, and imagery serve as vehicles for expressing a sense of national identity and cultural continuity. In particular, the paper emphasizes the use of traditional motifs and contemporary forms of expression, revealing how national coloristics shape the poetic discourse in post-Soviet Kazakhstan.The methodology is grounded in both literary analysis and cultural studies, offering a multi-dimensional approach that combines linguistic analysis with historical and sociopolitical context. By examining works of modern Kazakh poets such as Mukhtar Shakhanov, Olzhas Suleimenov, and others, the paper identifies key features of national coloristics, such as the use of color symbolism, natural imagery, and references to folklore and oral traditions. The study also investigates the role of language in negotiating the tension between global modernity and local tradition, a key concern in post-independence Kazakhstan.The research contributes to the growing body of work on the intersection of national identity and literary expression, proposing a framework for analyzing the role of coloristics as a medium through which poets engage with and shape national consciousness in contemporary Kazakhstan.